2020
DOI: 10.3390/foods9020206
|View full text |Cite
|
Sign up to set email alerts
|

Red Wine and Garlic as a Possible Alternative to Minimize the Use of Nitrite for Controlling Clostridium Sporogenes and Salmonella in a Cured Sausage: Safety and Sensory Implications

Abstract: The use of nitrite in meat products has been questioned due to its potential association with colon cancer. This work aimed to evaluate the behavior of Clostridium sporogenes (used as a surrogate for Cl. botulinum) and Salmonella in a dry-cured sausage, chouriço, made with and without nitrite and nitrate or with red wine and garlic, and to study the sensory implications through a consumer test. The survival of Cl. sporogenes and Salmonella was determined mainly by the reduction in water activity (aw), but the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 59 publications
0
22
1
2
Order By: Relevance
“…The addition of red wine (7.5%) to chouriço (dry-cured sausage) did not change the value of the redness parameter ( a *), which recorded the same high value as achieved with the addition of sodium nitrite (150 ppm). The authors also observed that red wine (7.5%) in combination with garlic (1%) increased the yellowness ( b *) of the product, which was thought to occur because of the interaction between the two ingredients [ 71 ]. Similar results were obtained for beef sausages treated with grape pomace (1% and 2%) combined with nitrite (30 mg/kg).…”
Section: Beneficial Effects Of Plant Extracts In Meat Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of red wine (7.5%) to chouriço (dry-cured sausage) did not change the value of the redness parameter ( a *), which recorded the same high value as achieved with the addition of sodium nitrite (150 ppm). The authors also observed that red wine (7.5%) in combination with garlic (1%) increased the yellowness ( b *) of the product, which was thought to occur because of the interaction between the two ingredients [ 71 ]. Similar results were obtained for beef sausages treated with grape pomace (1% and 2%) combined with nitrite (30 mg/kg).…”
Section: Beneficial Effects Of Plant Extracts In Meat Productsmentioning
confidence: 99%
“…Shin et al [ 83 ] reported that there were no coliform bacteria detected in pork patties. Patarata et al [ 71 ] noted that red wine in combination with garlic showed antibacterial activity against C. sporogenes and Salmonella in dry-cured sausages—chouriços. Similar results were obtained by Aquilani et al [ 82 ].…”
Section: Beneficial Effects Of Plant Extracts In Meat Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of aromatic ketones due to lipid oxidation is further associated with the characteristic aroma of cured meat products [60], and in products made with wine, the consumer associates the cured aroma to the characteristic wine aroma [8]. The aromatic compounds formed during curing and those from the seasoning might experience chemical modifications during storage, resulting in different intensities or perceptions of the aroma [61].…”
Section: Aging Testmentioning
confidence: 99%
“…There are several differences between the traditional recipes used to prepare cured loins and industrial production, namely the use of strategies to improve control over foodborne pathogens and to deal with meat with low amounts of fat that dry very easily. To ensure the control of pathogens, the use of nitrite contributes to the inhibition of Clostridium botulinum and Listeria monocytogenes, among others [8,9]. The problem associated with non-spore forming pathogens with low infective doses like Salmonella or enteropathogenic Escherichia coli is commonly overcome by the use of high microbial quality raw materials and application of mild heat treatments at the beginning of the drying [10,11].…”
Section: Introductionmentioning
confidence: 99%